2016
DOI: 10.1016/j.ibiod.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic dehalogenation of the chlorothalonil isomer o-tetrachlorophthalonitrile by Pseudochrobactrum sp. BSQ-1

Abstract: Microbial dehalogenation plays key roles in the biodegradation and detoxification of halogenated aromatics. Although the hydrolytic dehalogenation of halogenated aliphatic hydrocarbons and carboxylic acids has been extensively studied, there are few reports on the hydrolytic dehalogenation of halogenated aromatics. In this study, the aerobic strain BSQ-1, isolated from soils contaminated with halogenated aromatics in Jiangsu, China, was able to completely degrade 0.12 mM o-tetrachlorophthalonitrile in 84 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The main metabolites mainly include hydroxy chlorohydrin, 3-methoxycarbonyl-2,4,5,6tetrachlorobenzeneacetamide, methyl-2,5,6-trichloro-3-cyano-4-methoxy-benzoate, methyl-3-cyano-2,4,5,6-tetrachlorobenzoate, 4-sulfydryl-2,5,6-trichloroisophthalonitrile, 2-chloro-4,6-disulfydryl-5chloromethylisophthalonitrile, 2-chloro-4-sulfydryl-5-chloromethylisophthalonitril, etc. [20,23,37]. Here in this study, two degradation products were found in the microcosms after 4 days of incubation.…”
Section: Discussionsupporting
confidence: 53%
“…The main metabolites mainly include hydroxy chlorohydrin, 3-methoxycarbonyl-2,4,5,6tetrachlorobenzeneacetamide, methyl-2,5,6-trichloro-3-cyano-4-methoxy-benzoate, methyl-3-cyano-2,4,5,6-tetrachlorobenzoate, 4-sulfydryl-2,5,6-trichloroisophthalonitrile, 2-chloro-4,6-disulfydryl-5chloromethylisophthalonitrile, 2-chloro-4-sulfydryl-5-chloromethylisophthalonitril, etc. [20,23,37]. Here in this study, two degradation products were found in the microcosms after 4 days of incubation.…”
Section: Discussionsupporting
confidence: 53%
“…The dominant taxa that characterized the differences between bioremediation treatments and control included bacterial genera Pseudochrobactrum , Brevundimonas , and Bacillus and fungal genera Scedosporium , Stachybotrys , Microascus , and Acremonium . Pseudochrobactrum can degrade phenols ( Mao et al, 2015 ), halogenated aromatics ( Liu et al, 2016 ), and lignin ( Shannon et al, 2017 ), and Brevundimonas has the ability to degrade phenols ( Zhang et al, 2018 ). The dominant fungal genera have the ability to degrade lignin, cellulose, and PAHs ( Santos et al, 2006 ; López-González et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were first weighed and dissolved in sterile water. The concentration of trace metal ions in the inorganic salt medium was set to 0.2 mM based on a previous study in order for bacteria to maintain their normal growth [25]. The pH value was adjusted to 7.0 in the inorganic salt medium with both FH-1 bacterial suspension (5%) and Atrazine (50 mg L –1 ) added.…”
Section: Methodsmentioning
confidence: 99%